2020
DOI: 10.1002/open.202000275
|View full text |Cite
|
Sign up to set email alerts
|

CO2 Capture in Ionic Liquids Based on Amino Acid Anions With Protic Side Chains: a Computational Assessment of Kinetically Efficient Reaction Mechanisms

Abstract: Absorption and capture of CO 2 directly from sources represents one of the major tools to reduce its emission in the troposphere. One of the possibilities is to incorporate CO 2 inside a liquid exploiting its propensity to react with amino groups to yield carbamic acid or carbamates. A particular class of ionic liquids, based on amino acids, appear to represent a possible efficient medium for CO 2 capture because, at difference with current industrial setups, they have the appeal of a biocompat-ible and enviro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
41
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 15 publications
(42 citation statements)
references
References 38 publications
1
41
0
Order By: Relevance
“…The computational model has been previously verified as accurate enough when compared to CBS-QB3 and G4MP2 composite methods. 32 The Gaussian16 49 package was used for all the ab initio calculations. We have included the zero-point-energies in all of the energetic values reported in the rest of the paper.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…The computational model has been previously verified as accurate enough when compared to CBS-QB3 and G4MP2 composite methods. 32 The Gaussian16 49 package was used for all the ab initio calculations. We have included the zero-point-energies in all of the energetic values reported in the rest of the paper.…”
Section: Methodsmentioning
confidence: 99%
“…In principle, the kinetics of the reaction is therefore determined by the energy barrier along the PT step, but we have recently shown that, depending on the nature of the AA, there exist reactive pathways with null or negligible activation barriers. 32 …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Shaikh et al ( 2016 , 2020 ) showed the existence of barriers associated with the proton transfer step that leads the pre-reaction zwitterion to the final carbamate. Mercy et al ( 2016 ) and Onofri et al ( 2020 ) have found that the proton transfer step in [Ch][AA] can occur via two possible reaction pathways that differ by the size of the ring that is formed in the transition state as shown in Scheme 3 . The mechanism based on a 4-member ring is highly disfavored due to very high barriers, while the one with a 5-member ring has a low activation energy of only few kcal/mol.…”
Section: Chaail As Candidates For Co 2 Absorptionmentioning
confidence: 99%
“…Water seems to play a two-faced role since it works by reducing viscosity and hydrogen bonding, thus increasing the diffusion of CO 2 , as well as removing phenomena that render the reaction site less available, but it may also act as a catalyst for the overall CO 2 absorption reaction by assisting a more efficient PT. When a single water molecule was included in the transition state computational evaluation, it effectively lowered the kinetic barriers of this step (Li et al 2018 ; Shaikh et al 2020 ; Onofri et al 2020 ) by reducing the strain on the transition state cycle as shown in Scheme 4 .
Scheme 4 Possible mechanisms of the proton transfer step with a 6-member ring or a 7-member ring in the transition state when including a water molecule
…”
Section: Chaail As Candidates For Co 2 Absorptionmentioning
confidence: 99%